2014
DOI: 10.1063/1.4865480
|View full text |Cite
|
Sign up to set email alerts
|

Underwater acoustic omnidirectional absorber

Abstract: Gradient index media, which are designed by varying local element properties in given geometry, have been utilized to manipulate acoustic waves for a variety of devices. This study presents a cylindrical, two-dimensional acoustic “black hole” design that functions as an omnidirectional absorber for underwater applications. The design features a metamaterial shell that focuses acoustic energy into the shell's core. Multiple scattering theory was used to design layers of rubber cylinders with varying filling fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 21 publications
0
36
0
1
Order By: Relevance
“…Traditional underwater and ultrasound applications have achieved an impedance match by utilizing rubbers that have sound speeds less than water. While rubbers are used as components in transparent metafluid lattices [1], there have been other recent advances in acoustic impedance-matched designs. For example, negative-index complementary metamaterials are proposed to significantly enhance the transparency through aberrating materials [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditional underwater and ultrasound applications have achieved an impedance match by utilizing rubbers that have sound speeds less than water. While rubbers are used as components in transparent metafluid lattices [1], there have been other recent advances in acoustic impedance-matched designs. For example, negative-index complementary metamaterials are proposed to significantly enhance the transparency through aberrating materials [30].…”
Section: Discussionmentioning
confidence: 99%
“…GRIN geometries are utilized for a broad range of metamaterial applications including scattering reduction [6,7], wave focusing [8][9][10][11][12][13][14][15][16], and bending [1][2][3]17,18]. In contrast to previous lens designs, we present a lens composed of impedance-matched, hollow-shell elements with sound speeds higher than water.…”
Section: Introductionmentioning
confidence: 99%
“…1(a)]. In previous studies, 3,11,19,22,38 the inclusions of PCs are solid and the backgrounds are fluid. By contrast, the backgrounds of the present CGPCs are solid and the inclusions are fluid, and these CGPCs are porous cylinders with continuously graded structures.…”
Section: Methodsmentioning
confidence: 99%
“…34 Several studies have been devoted to the sound absorption characteristics of PCs, and have indicated that PCs could be employed to expand the content of sound absorption materials. [35][36][37][38] To the best knowledge of the authors, no research has been conducted on the sound absorption characteristics of CGPCs.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] It has now evolved into a powerful tool for designing a wide variety of new devices. [7][8][9][10][11][12] The most remarkable example is the invisibility cloak which has attracted great attention from researchers. [13][14][15] The acoustic invisibility cloak can make objects hard to detect acoustically.…”
Section: Introductionmentioning
confidence: 99%